Microdissected Pyramidal Cell Proteomics of Alzheimer Brain Reveals Alterations in Creatine Kinase B-Type, 14-3-3-γ, and Heat Shock Cognate 71 - Sandebring-Matton, Anna; Axenhus, Michael; Bogdanovic, Nenad; Winblad, Bengt; Schedin-Weiss, Sophia; Nilsson, Per; Tjernberg, Lars O. (Frontiers in Aging Neuroscience, 2021)
Novel insights on proteins involved in Alzheimer’s disease (AD) are needed. Since multiple cell types and matrix components are altered in AD, bulk analysis of brain tissue maybe difficult to interpret. In the current study, we isolated pyramidal cells from the cornu ammonis 1 (CA1) region of the hippocampus from five AD and five neurologically healthy donors using laser capture microdissection (LCM). The samples were analyzed by proteomics using 18O-labeled internal standard and nano-high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS) for relative quantification. Fold change between AD and control was calculated for the proteins that were identified in at least two individual proteomes from each group. From the 10 cases analyzed, 62 proteins were identified in at least two AD cases and two control cases. Creatine kinase B-type (CKB), 14-3-3-γ, and heat shock cognate 71 (Hsc71), which have not been extensively studied in the context of the human AD brain previously, were selected for further studies by immunohistochemistry (IHC). In hippocampus, semi-quantitative measures of IHC staining of the three proteins confirmed the findings from our proteomic analysis. Studies of the same proteins in the frontal cortex revealed that the alterations remained for CKB and 14-3-3-γ but not for Hsc71. Protein upregulation in CA1 neurons of final stage AD is either a result of detrimental, pathological effects, or from cell-specific protective response mechanisms in surviving neurons. Based on previous findings from experimental studies, CKB and Hsc71 likely exhibit protective effects, whereas 14-3-3-γ may represent a detrimental pathway. These new players could reflect pathways of importance for the development of new therapeutic strategies.